New Literacies of Online Reading Comprehension - Leu, Donald J.; Everett-Cacopardo, Heidi; Zawilinski, Lisa; McVerry, Greg; O'Byrne, W. Ian (The Encyclopedia of Applied Linguistics, 2012)
Literacy has become deictic (Leu, 2000); the meaning of literacy is rapidly changing as new technologies for literacy continually appear and new social practices of literacy quickly emerge.
Keywords: Internet; dept.cur; language in the classroom; literacy; online reading comprehension; reading